INSTITUTIONAL CHANGE AND ADAPTIVE BEHAVIOR IN HIGHER EDUCATION: THE CASE OF REFORMS IN UNDERGRADUATE ECONOMIC EDUCATIONIN RUSSIA - Vyacheslav V. Volchik (Высшее образование в России)
Institutional change in higher education is aimed at establishing a competitive and efficient system of specialist training. Institutional innovations tend to affect behavior patterns of major actors in this field. Institutional inertia and asynchronous change in formal and informal institutions can be viewed through the prism of adaptive behavior, which arises from existing institutional constraints.The institution of non-specialized undergraduate education influences and changes the basic principles of the educational process and the ways of organizing training programs. Meanwhile, this institution has been implemented for the purpose of developing the system of research training. The paper emphasizes the importance of analyzing adaptive behavior of students and lecturers in the context of institutional change, since that would provide better opportunities to adjustthe activities aiming atincreasing the effectiveness ofhigher education to existing institutions under conditions of rapid modernization and institutional import.